Seismic Vulnerability Assessment of Existing Reinforced Concrete Buildings in Urban Centers - Ferreira, Tiago Miguel (2020)
Despite the recent advances in the analysis of the seismic performance of reinforced concrete structures, the assessment of large building inventories aimed at defining and prioritizing structural retrofitting strategies is still a technically challenging task. This paper aims to contribute to bridging this gap by presenting a simplified methodology for assessing the seismic vulnerability of reinforced concrete buildings, which is then applied to a group of 91 buildings affected by recent earthquakes with different macroseismic intensities. The presented methodology is based on the evaluation of eight parameters associated with different factors that affect the seismic response of the building, namely its structural features, foundation conditions, and position within the urban mesh. The formulation of each parameter and the relative weight attributed to each one of them were defined on the basis of post-earthquake damage observation and expert opinion. After defined, the proposed methodology is applied to Faro city center. Based on the results obtained, a cost benefit analysis is made considering a strengthening solution to the buildings with soft-story irregularity.